The Role of Sharia Judges in Indonesia: Between The Common Law and The Civil Law Systems - Alfitri, Alfitri (Mazahib, 2017)
This article seeks to analyse the role of Religious Courts’ (Pengadilan Agama or PA) Judges in the formation of Islamic law in Indonesia. As part of the civil legal system, PA Judges are bound by legal provisions in handling legal disputes in court. They must apply the applicable legal provisions to decide upon a case. This condition can also be understood from the aspect of appointment of judges in Indonesia, including PA Judges, which is conducted not through professional career path as in the common law system. Thus, they are appointed from a new graduate of law/sharia faculty and then trained, inter alia, to apply and/or interpret applicable laws (legislation); and not to make the law itself. However, on the basis of secondary data analysis, studies on the ijtihad of PA Judges reveal that they are no longer only fixated on the provisions of statutes in deciding cases. They also make laws, cases in point are the Compilation of Islamic Law (KHI) and the Compilation of Sharia Economic Law (KHES), do ijtihad on the books of fiqh which became the basis for the drafting of Islamic legislation in Indonesia. Some of them even do direct ijtihad from Sharia sources, namely the Qur'an and Hadith. This condition is arguably more in accordance with the character of judges (qadis) in Islamic history which on a certain level similar to the role of judges in common law system.Keywords: Sharia Judges’ Role, Legal Profession, Bureaucracy, Common Law System, Civil Law System